KEPUTUSAN PETANI BERALIH USAHATANI DARI TANAMAN KAKAO MENJADI LADA DI KABUPATEN LAMPUNG TIMUR - Zulkarnain Zulkarnain; Muher Sukmayanto (Mimbar Agribisnis: Jurnal Pemikiran Masyarakat Ilmiah Berwawasan Agribisnis, 2019)
This study aims to determine the decision of farmers to switch farming from cocoa plants to pepper plants in East Lampung Regency. The location of this study was conducted in Sukadana District and Margatiga District, East Lampung Regency. Respondents in this study were pepper farmers and cocoa farmers in Sukadana District and Margatiga District, East Lampung Regency, as many as 67 farmers who were selected by simple random sampling. To answer the research objectives, it is logit analysis. The results of the research obtained are factors that influence farmers' decision to switch farming from cocoa to pepper crops they are farmer's age, family dependence, farming experience, and income.